Supernumerary teeth classification: a literature review - Cruz, Edison Andrés (Revista Estomatología, 2014)
Supernumerary teeth are a variation of the number and morphology of teeth which its etiology has not been completely understood. They could be found not only in the maxilla and jaw but in ectopic locations thus, becoming difficult the diagnosis and treatment. Due to its role in the formation of diastema, crowding, cyst, root resorption, tooth impaction, it is important to use a diagnosis guide that lead the selection of proper treatment for the patient. The objective of this review article is to provide a contemporary appraisal focused on the diagnosis, classification and management of supernumerary teeth, in order to aid clinical decision-making.